Complications of a Fenestrated Endovascular Aortic Aneurysm Repair (EVAR): A case study and fi rst experience of National Institute of Cardiovascular Diseases Hospital, Dhaka - M Islam; NC Mandal; AHM Bashar; A Hoque; MM Rahman; SK Ghosh (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2018)
Endovascular aneurysm repair (EVAR) has revolutionized the therapeutic strategy for abdominal aortic aneurysm (AAA). However, hostile proximal neck and tortousity of access remain a challenge in selecting optimal stent grafts in AAA. Although EVAR is obviously less invasive then open surgical procedure, it is not free of complications. This can potentially result in severe morbidity and mortality.